The Effect of Wetland Geography on the Prevalence of Diabetes Mellitus in South Kalimantan - Fajari, Nanang Miftah; Nur’amin, Hendra Wana (Fakultas Kedokteran Universitas Lambung Mangkurat, 2023)
Diabetes mellitus (DM) is a high-burden disease in Indonesia especially in South Kalimantan Province. South Kalimantan province lies in mostly wetlands areas. Identification of risk factors related to DM is necessary to prevent the disease. We conducted this study to assess the prevalence of DM in the South Kalimantan people, the impact of a wetlands area on DM prevalence, and other significant risk factors. A cross-sectional study approach was used to identify significant risk factors. We used adjusted multiple logistic regression to assess the association between risk factors and DM prevalence. There were 4612 subjects more than 18 years old in this study with 6.5% of them diagnosed as DM. Most of the subjects live in wetlands area (79.1%) and most of them >40 years old. Several important risk factors associated with DM were identified. Subjects in wetlands have a lower risk of DM compared to non-wetlands area (OR 0.73, CI 95%; 0.43-0.71, p<0.001). Age >40 years old increase the risk of DM (OR 2.24, CI 95 % 1.61-3.10, p<0.001), hypertension (OR 1.65, CI 95% 1.23-2.21, p<0,001), waist circumference >90 cm (OR 2.12, CI 95%. p<0.001), cholesterol level (>200 mg/dl) with DM prevalence (OR 1.38, CI 95% 1.02-1.87, p<0.04) and family history of DM (OR 10.28, CI 95% 7.67-13.76, p<0.001). This study found that wetlands areas may reduce the DM prevalence and other risk factors may increase the prevalence of DM. Further research is necessary to establish the relationship between wetlands area and DM.